2001
DOI: 10.1097/00005373-200109000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Induces Human Mononuclear Cell Arginase I Expression

Abstract: Increased MNC arginase expression may contribute to postsurgical immune dysfunction by affecting arginine use and availability and nitric oxide metabolism in the immune system. Plasma IL-10 may play a role in regulating MNC arginase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…On an initially empiric basis, oral arginine supplementation was explored and found to show efficacy for improving immune function in patients suffering major trauma or undergoing extensive surgical procedures (28). It was subsequently confirmed that ArgI is transiently found at increased levels in these patients (29,30), supporting the clinical utility for dietary L-arginine supplementation in the reversal of immunosuppression. These clinical results encourage parallel translation to patients with cancer.…”
Section: Discussionmentioning
confidence: 68%
“…On an initially empiric basis, oral arginine supplementation was explored and found to show efficacy for improving immune function in patients suffering major trauma or undergoing extensive surgical procedures (28). It was subsequently confirmed that ArgI is transiently found at increased levels in these patients (29,30), supporting the clinical utility for dietary L-arginine supplementation in the reversal of immunosuppression. These clinical results encourage parallel translation to patients with cancer.…”
Section: Discussionmentioning
confidence: 68%
“…73,106 We have made nearly identical observations in humans after surgery and in mouse models of surgical trauma (data not shown). 74,100,101 Therefore, a wealth of data supports the hypothesis that arginine deficiency developed through increased ASE I expression may be modulating nitric oxide production in vivo. Peritoneal mouse macrophages (2ϫ10 6 cells/mL) were placed in culture.…”
Section: Arginine In Myeloid Cellsmentioning
confidence: 88%
“…100 Shortly thereafter, we demonstrated dramatic increases in ASE I expression in peripheral mononuclear cells in severely traumatized victims and also in patients undergoing elective surgery, demonstrating that alterations in arginine metabolism in the immune system are evolutionarily conserved across species. 74,101 ASE I exhibits 2 important biologic functions. The first is that it generates ornithine and urea from its substrate arginine.…”
Section: Arginine In Myeloid Cellsmentioning
confidence: 99%
“…However, the normalization of arginase activity occurred in lower percentage of patients (57% in CRC, 42% in CRCLM) than that of L-arginine (about 70% in both groups). Because trauma increases arginase activity and surgery induces arginase expression [28,29], the reason of such discrepancy may be the surgical procedure itself.…”
Section: Discussionmentioning
confidence: 99%